PCR protocols : current methods and aplications - White, Bruce A (Humana Press, 1993)
University of Connecticut, Farmington. Methods in Molecular Biology, Volume 15. Selective manual of analytical and preparative protocols in polymer chain reaction (PCR). Plastic spiral binding. 67 contributors, mostly U.S.
Methods in molecular biology ; Vol. 15
Keywords: Clinical Laboratory Techniques; molekulární biologie, molekulární medicína; klinické laboratorní techniky; polymerázová řetězová reakce; PCR; Polymerase Chain Reaction